Remembering with emotion in dynamic psychotherapy : new directions in theory and technique - Sandler, Steven B., 1948- (Jason Aronson, 2011)
This book provides a new look at dynamic psychotherapy, re-examining its basic theory and challenging the limits of current models. Making use of emotion theory, attachment theory, and memory theory, this book is in line with the current trend of psychotherapy writers, integrating diverse fields of study.